Peran Marketing Terhadap Omset Penjualan UMKM - Wita Setiawati; Sofi Mutiara Insani; Syarifah Setiana Ardiati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research explores the important role of marketing in increasing the sales turnover of Micro, Small and Medium Enterprises (UMKM) in Indonesia. The article outlines effective marketing strategies, including the implementation of digital marketing, branding, the right pricing strategy, and the role of promotions in attracting customers. Through a literature study, it is found that the implementation of the right marketing strategies can significantly increase the visibility of UMKM and optimise their sales performance. The results show that UMKM that adopt digital marketing can experience an increase in turnover of up to 50%. This research highlights the importance of government support and collaborative efforts to improve UMKM access to marketing training and information. It is hoped that this article provides useful insights for UMKM players and relevant stakeholders to develop more effective and sustainable marketing strategies.